Lower extremity muscle functions during full squats - Robertson, D. G. E.; Wilson, J. M. J.; St. Pierre, T. A. (Journal of Applied Biomechanics, 2008)
The purpose of this research was to determine the functions of the gluteus maximus, biceps femoris, semitendinosus, rectus femoris, vastus lateralis, soleus, gastrocnemius, and tibialis anterior muscles about their associated joints during full (deep-knee) squats. Muscle function was determined from joint kinematics, inverse dynamics, electromyography, and muscle length changes. The subjects were six experienced, male weight lifters. Analyses revealed that the prime movers during ascent were the monoarticular gluteus maximus and vasti muscles (as exemplified by vastus lateralis) and to a lesser extent the soleus muscles. The biarticular muscles functioned mainly as stabilizers of the ankle, knee, and hip joints by working eccentrically to control descent or transferring energy among the segments during scent. During the ascent phase, the hip extensor moments of force produced the largest powers followed by the ankle plantar flexors and then the knee extensors. The hip and knee extensors provided the initial bursts of power during ascent with the ankle extensors and especially a second burst from the hip extensors adding power during the latter half of the ascent.